A Review of Coccidiosis in Small Ruminant and Antiparasitic Activity of Essential Oils : - - nurdianti, Nurdianti (Universitas Airlangga, 2023)
Coccidiosis have been reported to cause severe economic losses in small ruminants livestock industry. Subclinical coccidiosis is common among small ruminants and clinical occurs mainly in young's animals. Coccidiosis is caused by highly host-specific Eimeria species. Strategies to control traditionally rely on the use of management practices combined with anticoccidial treatments. The development of alternative, safer, and ecofriendly anticoccidial agents have become priority in most parts of the world. Essential oils have been shown to exhibit antiparasitic activity and may control protozoal pathogens. The purpose of this review is to provide an overview of Eimeria species in sheep and goats and demonstrated life cycle, clinical signs, diagnosis, treatment and potency use of essential oils in the treatment of coccidiosis.